Особливості побудови моделі соціально орієнтованої національної економіки - Головня, О.М.; Кінаш, І.П. (Економіка природокористування і сталий розвиток, 2020)
Здійснено аналіз передумов розробки моделі розвитку економіки України в контексті соціальної орієнтованості з урахуванням взаємозумовленого впливу механізму ринкових відносин та економічної політики держави.
Досліджено, що господарський механізм соціально орієнтованої ринкової економіки містить організаційну структуру виробництва (вертикальну та горизонтальну), конкретні форми функціонування економічної системи (державного і недержавного регулювання ринку), а також інституціональну базу (включаючи її законодавчу складову). Визначено, що в умовах побудови нової моделі національної економіки підвищується роль недержавних та благодійних організацій. Виділено роль громадських організацій як одну з найбільш оптимальних правових форм допомоги населенню у вирішенні спільних проблем і відстоюванні спільних інтересів, котра є обов’язковим атрибутом досліджуваної моделі. The background of the development of the model of economic development of Ukraine in the context of social orientation has been analyzed taking into account the interdependent influence of the mechanism of market relations and economic policy of the state.
It is researched that the economic mechanism of socially oriented market economy contains organizational structure of production (vertical and horizontal), specific forms of functioning of economic system (state and non-state regulation of the market), as well as a specific institutional base (including its legislative component). The constituents of the economic system are entities formed by large economic entities (eg financial corporations).
The authors argue that the economic mechanism of a socially oriented national economy is a complex structure and system of interconnections and includes: a) a system of balanced markets; b) public sector of economy; c) large economic structures that fulfill the regulatory role of the state for the economy as a whole and at the same time increase the market sensitivity to medium and long-term programs of its development; d) public sector administrative and production subsystem; e) system of operative state regulation of economy; e) a budget-balancing system with a powerful core; g) regulatory framework governing mid-market processes.
The study states that Ukraine, in rather difficult conditions, produces the parameters of its own national model of socio-economic development for the long term. The country has not yet formulated or implemented an effective model of economic development that would fully reflect its national characteristics and interests and become a macroeconomic basis for effective state regulation
It is determined that in the conditions of construction of a new model of the national economy the role of non-governmental and charitable organizations is increasing. The role of non-governmental organizations, which represent one of the most optimal legal forms to assist citizens in solving their common problems, upholding common interests, is a compulsory attribute of the model of socially oriented national economy.